2022
DOI: 10.1021/acs.biochem.1c00710
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of a T7 Bacteriophage Endolysin Variant with Enhanced Amidase Activity

Abstract: The therapeutic use of bacteriophage-encoded endolysins as enzybiotics has increased significantly in recent years due to the emergence of antibiotic resistant bacteria. Phage endolysins lyse the bacteria by targeting their cell wall. Various engineering strategies are commonly used to modulate or enhance the utility of therapeutic enzymes. This study employed a structure-guided mutagenesis approach to engineer a T7 bacteriophage endolysin (T7L) with enhanced amidase activity and lysis potency via replacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Endolysins are peptidoglycan-lysing enzymes and expressed at the end of the lytic cycle of bacteriophages for release of assembled progeny. Exogenous treatment has demonstrated that recombinant endolysins are novel antimicrobials, and various recombinant endolysins are being assessed in clinical trials [ 18 , 19 , 20 ]. Modular endolysins are composed of various enzymatic domains and cell-wall-binding domains that have independent activities [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endolysins are peptidoglycan-lysing enzymes and expressed at the end of the lytic cycle of bacteriophages for release of assembled progeny. Exogenous treatment has demonstrated that recombinant endolysins are novel antimicrobials, and various recombinant endolysins are being assessed in clinical trials [ 18 , 19 , 20 ]. Modular endolysins are composed of various enzymatic domains and cell-wall-binding domains that have independent activities [ 21 ].…”
Section: Introductionmentioning
confidence: 99%